Limited Diffusion and Cell Dimensions in a Micrometer Layer of Solution: An Electrochemical Impedance Spectroscopy Study. Issue 8 (12th April 2017) - Botasini, Santiago; Méndez, Eduardo
Abstract: The electrochemical impedance behavior observed for a newly proposed electrochemical system [Botasini et al., Analyst, 2016, 141, 5996–6001], in which the complete electrodic system is screen‐printed on the same plane and homogeneously covered by a thin layer of solution, was studied in a wide frequency domain (10 mHz to 100 kHz) involving 127 logarithmically spaced frequencies. Two distinctive frequency domain behaviors were considered, with the addition of a series‐connected capacitor, representing the physical limit of the electrochemical cell. Two diffusion regimes for the electroactive species were detected: i) semi‐infinite linear diffusion close to the electrode surface and limited by a reflecting boundary, followed by ii) distorted diffusion corresponding to the bulk solution enclosed within the thin‐layer cell. From the electric circuit parameters, the diffusion length of the semi‐infinite linear diffusion process, the heterogeneous rate constant for the charge transfer, and the width of the thin‐layer experimental cell can be calculated. For the first time, electrochemical impedance spectroscopy analysis provides a thorough means to study limited diffusion in micrometer‐sized layer that includes the physical limit of the electrochemical cell. All these data are fundamental in the design of novel micro‐ and nano‐fluidic systems. Abstract : Just a drop : The current distribution lines between the counter and working electrodes under thin‐layer conditions are induced by a drop of solution under a coverslip weight. The annotated distances correspond to the solid electrode width (10 μm), the diffusion length under the Warburg limited diffusion (ca. 1.5 μm), and the electrochemical thin‐layer cell (ca. 25 μm).